2021
DOI: 10.3855/jidc.13573
|View full text |Cite
|
Sign up to set email alerts
|

An unequivocal superbug: PDR Klebsiella pneumoniae with an arsenal of resistance and virulence factor genes

Abstract: Introduction: Infections caused by extensively-drug resistant (XDR) and pan-drug resistant (PDR) Klebsiella pneumoniae represent an emerging threat due to the high associated mortality. This study aimed to characterize two carbapenem resistant K. pneumoniae strains from the same patient, the first being PDR (referred to as IMP 1078b) and the second being XDR (referred to IMP 1078s) isolated from the same patient. Methodology: Antimicrobial susceptibility testing was done for the 2 K. pneumoniae isolates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…In this study, the results of antibiotic susceptibility testing (AST) revealed that a relatively high proportion (more than 50.0%) of cKp and hvKp isolates were resistant to aminoglycosides, beta-lactam combination agents (piperacillin-tazobactam and ampicillin/sulbactam), quinolones, folate pathway inhibitors, and different classes of cephalosporins. These findings were consistent with recent reports of increasing emergence of highly resistant XDR and PDR cKp and hvKp strains from different countries, including Iran, Turkey, Spain, India, Saudi Arabia, and Lebanon ( Örsten et al, 2020 ; Ballén et al, 2021 ; Banerjee et al, 2021 ; Sleiman et al, 2021 ; Badger-Emeka and Emeka, 2022 ; Davoudabadi et al, 2022 ). Generally, this can be explained by the presence of mobile genetic elements (MGEs) harboring several antibiotic resistance genes including IncFI, ColKP3, and IncR plasmids in the cKp and hvKp isolates ( Xanthopoulou et al, 2020 ; Banerjee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the results of antibiotic susceptibility testing (AST) revealed that a relatively high proportion (more than 50.0%) of cKp and hvKp isolates were resistant to aminoglycosides, beta-lactam combination agents (piperacillin-tazobactam and ampicillin/sulbactam), quinolones, folate pathway inhibitors, and different classes of cephalosporins. These findings were consistent with recent reports of increasing emergence of highly resistant XDR and PDR cKp and hvKp strains from different countries, including Iran, Turkey, Spain, India, Saudi Arabia, and Lebanon ( Örsten et al, 2020 ; Ballén et al, 2021 ; Banerjee et al, 2021 ; Sleiman et al, 2021 ; Badger-Emeka and Emeka, 2022 ; Davoudabadi et al, 2022 ). Generally, this can be explained by the presence of mobile genetic elements (MGEs) harboring several antibiotic resistance genes including IncFI, ColKP3, and IncR plasmids in the cKp and hvKp isolates ( Xanthopoulou et al, 2020 ; Banerjee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Also, the majority of the carbapenem-resistant isolates (84.3%, n = 70/83) had a MARI of ≥0.5 and no PDR isolate was detected. In contrast to the current study, in previous reports by Örsten et al (2020) from Turkey, Davoudabadi et al (2022) from Iran, and Banerjee et al (2021) from India, XDR and PDR CR-hvKp isolates have been reported. The lack of integrated stewardship programs for antibiotic use and prescribing and the sale of antibiotics in pharmacies without a doctor's prescription are among the reasons for the increasing antibiotic resistance rates in GNB, especially in third world countries (Sharma et al, 2022).…”
Section: Beta-lactamase Determinants Total Carbapenem-resistantcontrasting
confidence: 99%
See 1 more Smart Citation
“…Many review articles have been published about multidrug-resistant bacteria and treatment strategies employed to combat them. However, most of these articles focus on a particular resistant bacteria or a specific line of treatment [5][6][7][8][9]. Moreover, in the continuous fight against emerging MDR bacterial species, knowledge updating is highly recommended for researchers and medical professionals.…”
Section: Introductionmentioning
confidence: 99%
“…This is the result of difficulties in treating strains of K. pneumoniae that exhibit multidrug resistance (MDR) to available antibiotics. Additionally, disturbing is the heavy disease burden attributed to this bacterium in critically ill patients [11], thus leading to poor treatment outcomes [12][13][14]. Moreover, K. pneumonia infections are associated with extended hospital stays, along with subsequent high mortality rates resulting from isolates that are extremely resistant (XDR) against most or sometimes all antibiotics [15].…”
Section: Introductionmentioning
confidence: 99%